Resistance of polypropylene-wood composites to fungi - Cofta, G.; Borysiak, S.; Doczekalska, B.; Garbarczyk, J. (Polimery, 2022)
In the present study, the composites of polypropylene and wood were prepared. The experimental material comprised two most common Polish timber species pine wood (Pinus sylvestris L.) as a softwood species and oak wood (Quercus sp.) as a hardwood species. The size of wood sawdust ranged from 0.5 to 1.0 mm. Two types of lignocellulosic materials were used in the experiments described: wood without any previous chemical treatment and wood after its mercerization (i.e. activated with NaOH). In addition the polypropylene-wood composite containing a block copolymer, i.e. styrene-ethylene-butylene-styrene (SEBS) was also obtained. The objective of this study was to evaluate the resistance of different kinds of polypropylene-wood composites to fungal decay. Weight losses and temporary tensile strength of composite samples after the mycological test were determined.